2018
DOI: 10.1007/s11218-018-9457-7
|View full text |Cite
|
Sign up to set email alerts
|

Bullying and its association with altruism toward victims, blaming the victims, and classroom prevalence of bystander behaviors: a multilevel analysis

Abstract: With reference to social-ecological, self-determination, attributional, and social cognitive theories, the current study examined whether gender, age, altruistic motivation to defend victims, and tendency to blame the victims, at the individual level, and the prevalence of reinforcing and defending, at the classroom level, were associated with bullying. A sample of 901 Swedish students (9-13 years old, M = 11.00, SD = .83) from 43 classrooms filled out a questionnaire. Multilevel regression analyses revealed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
42
1
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 52 publications
(57 citation statements)
references
References 65 publications
2
42
1
2
Order By: Relevance
“…Finally, it has been observed that the inclusion of the figure of the bystander in the analysis was fundamental, given that the prevalence of attending situations of relational aggressions or bullying through the Internet was reduced when relations with the environment were more positive, in the same proportion as preventing aggresions and victimization. This fact that calls for a greater attention to this figure, as already claimed by Thornberg and Wänström (2018) or Olenik-Shemesh et al (2017).…”
Section: Discussionmentioning
confidence: 68%
See 2 more Smart Citations
“…Finally, it has been observed that the inclusion of the figure of the bystander in the analysis was fundamental, given that the prevalence of attending situations of relational aggressions or bullying through the Internet was reduced when relations with the environment were more positive, in the same proportion as preventing aggresions and victimization. This fact that calls for a greater attention to this figure, as already claimed by Thornberg and Wänström (2018) or Olenik-Shemesh et al (2017).…”
Section: Discussionmentioning
confidence: 68%
“…In the case of the latent variables of "Peer Victimization" and "Bully Perpetration", Rawlings uses The University of Illinois Aggression Scales (Espelage & Holt, 2001) to assess the occurrence of bullying behavior and victimization by peers, and the Internet Harassment Victimization scale and Internet Harassment Perpetration scale, both by Ybarra, Espelage, and Mitchell (2007), to assess those cyberbullying behaviors. Using a lickert scale 1-5 (from never to 7 times or more), these variables measure the frequency of aggressions and cyber-aggressions in victims such as "my classmates made fun of me" or "they call me names", and in bullies, as "upset" or "exclude" (see Figure 1) Based on the theory by Bronbrenbrenner's and the empirical work by Rawlings (2017), in the present research we set out to analyze the influence of the micro and meso-level relationships in the behaviors of aggression and victimization of bullying and cyberbullying, following Fettrow (2013) or Hong and Espelage (2012), and adding the figure of the bystander, being an agent so far less analyzed by the literature, but with a relevance demonstrated by authors such as Thornberg andWänström (2018) for bullying, or Olenik-Shemesh et al (2017) for cyberbullying. Following Thornberg and Wänström (2018), if we take into account socio-ecological theories in the explanation of bullying situations, we cannot ignore the role of bystander as a relevant agent in blaming the victims (reinforcing bullying behaviors) or defending and reinforcing them(preventing aggressions).…”
Section: Hypothetical Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…Our results show bullying relates to heightened activation in neural regions associated with motivation and salience when viewing such circumstances, suggesting that when considering why individuals engage in such acts, a lack of socioemotional awareness on behalf of the perpetrator may be unwarranted. Instead, these findings highlight the role that social interventions may be able to play: if bullies are aware of what they are doing, then moving away from perceived "deficiencies" and instead devoting resources to studying the system level buffers which may push individuals towards or away from aggressing is crucial (Salmivalli, Voeten, & Poskiparta, 2011;Thornberg & Wänström, 2018). Social componentssuch as classroom culture, adult supervision or intervening classmatescan help mitigate the worst expressions of bullying (Chan et al, 2016) but have not been examined via neuroscience paradigms.…”
Section: Discussionmentioning
confidence: 99%
“…Being defended matters for youth who are bullied, because they are more likely to escape from an escalating circle of bullying (Hawkins et al 2001;O'Connell et al 1999) and they are less likely to suffer from mental health problems compared to their non-defended peers (Juvonen et al 2016;Sainio et al 2010). Defending also matters on the class level, because in classes where defending is supported by descriptive and injunctive norms, bullying rates are lower (Pozzoli et al 2012;Salmivalli et al 2011;Thornberg and Wänström 2018).…”
Section: Why Bystander Behavior Matters In Bullying Situationsmentioning
confidence: 99%